2010
DOI: 10.1128/aem.02188-09
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Nitrogen Reductase and Nitrite Reductase Genes in Soil of Thinned and Clear-Cut Douglas-Fir Stands by Using Real-Time PCR

Abstract: The abundance of nifH, nirS, and nirK gene fragments involved in nitrogen (N) fixation and denitrification in thinned second-growth Douglas-fir (Pseudotsuga menziesii subsp. menziesii [Mirb.] Franco) forest soil was investigated by using quantitative real-time PCR. Prokaryotic N cycling is an important aspect of N availability in forest soil. The abundance of universal nifH, Azotobacter sp.-specific nifH (nifH-g1), nirS, and nirK gene fragments in unthinned control and 30, 90, and 100% thinning treatments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 53 publications
2
26
1
Order By: Relevance
“…(). The nifH genes have been reported to be present in good numbers in various terrestrial habitats (Levy‐Booth & Winder, ; Xiao et al ., ). The saline soils are devoid of vegetation, and therefore lower cycling of organic matter is expected, which allows diazotrophs to flourish.…”
Section: Discussionmentioning
confidence: 99%
“…(). The nifH genes have been reported to be present in good numbers in various terrestrial habitats (Levy‐Booth & Winder, ; Xiao et al ., ). The saline soils are devoid of vegetation, and therefore lower cycling of organic matter is expected, which allows diazotrophs to flourish.…”
Section: Discussionmentioning
confidence: 99%
“…A positive relationship between amount of organic C and abundance of some functional groups of denitrifiers was observed (Barta et al, 2010;Chen et al, 2010;Dandie et al, 2008;Kandeler et al, 2006;Levy-Booth and Winder, 2010). It was reported that the source of organic C changed the composition of denitrifier communities: i.e.…”
Section: Introductionmentioning
confidence: 88%
“…The qPCR methods were used to determine the abundance of amoA, cbbL, nifH, etc. genes from marine environments and agriculture soils (He et al, 2007;Levy-Booth and Winder, 2010;Selesi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%